Značilnosti političnega govora v totalitarni in demokratični družbi - Kernc, Boštjan (Jezik in slovstvo, 2005)
In the first part the article summaries some expert opinions on the role of political (parliamentary) discourse and the linguistic features that faciliate the performance of these roles. The second part of the article presents the results of a study involving speeche bz Slovene MPs in four different periods of the totaitarian regime (1950, 1968, 1975, 1988) and one in the democratic system (2001). The analyses of the most relevant lexical and gramatical elements aims to show how the influence of a political system and historical circumstances is reflected in linguistic expressions, focusing on the comparison of the features by the speeches from the totalitarian and those from the democtaric era.
Keywords: democracy; demokracija; govori; history; politični jezik; Slovene; slovenščina; tekstna lingvistika; totalitarianism; totalitarizem; zgodovina